The fractional and nonlinear magneto-flexible rod - David, S. A.; Balthazar, José Manoel [UNESP]; Julio, B. H S; Oliveira, C. (IOP Publishing, 2012)
This paper deals with a system involving a flexible rod subjected to magnetic forces that can bend it while simultaneously subjected to external excitations produces complex and nonlinear dynamic behavior, which may present different types of solutions for its different movement-related responses. This fact motivated us to analyze such a mechanical system based on modeling and numerical simulation involving both, integer order calculus (IOC) and fractional order calculus (FOC) approaches. The time responses, pseudo phase portraits and Fourier spectra have been presented. The results obtained can be used as a source for conduct experiments in order to obtain more realistic and more accurate results about fractional-order models when compared to the integer-order models. © Published under licence by IOP Publishing Ltd.
Keywords: External excitation; Fourier spectra; Fractional-order calculus; Integer order; Magnetic force; Mechanical systems; Nonlinear dynamic behaviors; Pseudo-phase; Time response; Calculations; Vibration analysis